Complex molecular and functional outcomes of single versus sequential cytokine stimulation of rat microglia. Issue 1 (December 2016) - Siddiqui, Tamjeed; Lively, Starlee; Schlichter, Lyanne
Abstract Background Microglia are the "professional" phagocytes of the CNS. Phagocytosis is crucial for normal CNS development and maintenance, but it can be either beneficial or detrimental after injury or disease. For instance, white matter damage releases myelin debris that must be cleared by microglia in order for re-myelination to occur. However, phagocytosis can also produce damaging reactive oxygen species (ROS). Furthermore, microglia can acquire pro-inflammatory (M1) or anti-inflammatory (M2) activation states that affect cell functions. Although microglia are exposed to a changing cytokine environment after injury or disease, little is known about the molecular and functional consequences. Therefore, we applied several microglial activation paradigms, with or without myelin debris. We assessed(i) gene expression changes reflecting microglial activation and inflammatory states, and receptors and enzymes related to phagocytosis and ROS production, (ii) myelin phagocytosis and production of ROS, and(iii) expression and contributions of several ion channels that are considered potential targets for regulating microglial behavior. Methods Primary rat microglia were exposed to cytokines, individually or sequentially. First, responses to individual M1 or M2 stimuli were compared: IFN-γ plus TNF-α ("I + T"; M1 activation), interleukin-4 (M2a/alternative activation), and interleukin-10 (M2c/acquired deactivation). Second, sequential cytokine addition was used to assess microglia repolarization and cell functions. The paradigms were M2a→M1, M2c→M1, M1→M2a, and M1→M2c. Results M1 stimulation increased pro-inflammatory genes, phagocytosis, and ROS, as well as expression of Kv1.3, KCa3.1, and Kir2.1 channels. M2a stimulation increased anti-inflammatory genes, ROS production, and Kv1.3 and KCa3.1 expression. Myelin phagocytosis enhanced the M1 profile and dampened the M2a profile, and both phagocytosis and ROS production were dependent on NOX enzymes and Kir2.1 and CRAC channels. Importantly, microglia showed some capacity for re-polarization between M1 and M2a states, based on gene expression changes, myelin phagocytosis, and ROS production. Conclusions In response to polarizing and re-polarizing cytokine treatments, microglia display complex changes in gene transcription profiles, phagocytic capacity, NOX-mediated ROS production, and in ion channels involved in microglial activation. Because these changes might affect microglia-mediated CNS inflammation, they should be considered in future experimental, pre-clinical studies.